Influence of dry ice blasting process properties on surface roughness and residual stresses of machined and additive manufactured workpieces - Amon, Sven; Jobst, Andreas; Merklein, Marion; Hanenkamp, Nico (Procedia CIRP, 2022)
Dry ice blasting has shown the potential to remove metallic burrs after machining processes and support structures after additive manufacturing. During blasting, process parameters need to be chosen depending on the material and the geometric properties of the burr. However, dry ice blasting affects the local material properties on a micro level and improper blasting parameters may lead to changes in the part surface. In this article, correlations and interactions between dry ice blasting parameters and resulting specimen roughness and residual stresses are identified for machined and additive manufactured metallic materials.<br
Keywords: dry ice blasting; metallic edge zone; deburring; post-processing; residual stresses